2021
DOI: 10.1021/acs.est.0c03685
|View full text |Cite|
|
Sign up to set email alerts
|

Halogen Radicals Contribute to the Halogenation and Degradation of Chemical Additives Used in Hydraulic Fracturing

Abstract: In hydraulic fracturing fluids, the oxidant persulfate is used to generate sulfate radical to break down polymer-based gels. However, sulfate radical may be scavenged by high concentrations of halides in hydraulic fracturing fluids, producing halogen radicals (e.g., Cl•, Cl2 •–, Br•, Br2 •–, and BrCl•–). In this study, we investigated how halogen radicals alter the mechanisms and kinetics of the degradation of organic chemicals in hydraulic fracturing fluids. Using a radical scavenger (i.e., isopropanol), we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 77 publications
4
13
0
Order By: Relevance
“…Other one-electron oxidizing radicals such as CO 3 •– and Cl 2 •– may of course have analogous effects. CO 3 •– and Cl 2 •– can be formed not only in AOPs by reactions of HO • and SO 4 •– with HCO 3 – /CO 3 2– and Cl – but also in sunlit surface water by the natural organic matter photosensitized reactions in the presence of HCO 3 – /CO 3 2– and Cl – . ,,, Recently, Song’s group reported that DOM can inhibit the transformation rate of cyanotoxin by reducing its oxidized intermediates produced by CO 3 •– . This suggests that further study of any analogous effect of DOM is needed in both sunlit natural waters and engineered water-treatment processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other one-electron oxidizing radicals such as CO 3 •– and Cl 2 •– may of course have analogous effects. CO 3 •– and Cl 2 •– can be formed not only in AOPs by reactions of HO • and SO 4 •– with HCO 3 – /CO 3 2– and Cl – but also in sunlit surface water by the natural organic matter photosensitized reactions in the presence of HCO 3 – /CO 3 2– and Cl – . ,,, Recently, Song’s group reported that DOM can inhibit the transformation rate of cyanotoxin by reducing its oxidized intermediates produced by CO 3 •– . This suggests that further study of any analogous effect of DOM is needed in both sunlit natural waters and engineered water-treatment processes.…”
Section: Resultsmentioning
confidence: 99%
“…•− with HCO 3 − /CO 3 2− and Cl − but also in sunlit surface water by the natural organic matter photosensitized reactions in the presence of HCO 3 − /CO 3 2− and Cl − . 32,53,61,62 Recently, Song's group reported that DOM can inhibit the transformation rate of cyanotoxin by reducing its oxidized intermediates produced by CO 3…”
Section: ■ Introductionmentioning
confidence: 99%
“…The radicals generated in this process can also oxidize and degrade organic pollutants in the hydraulic fracturing fluid. As previously discussed by many researchers, persulfate activation by iron (zero-valent iron and pyrite) can effectively reduce the levels of various harmful additives in fracturing fluids and reduce the environmental risk of fracturing fluids. , Moreover, a recent study also demonstrated the transformation of SO 4 •– radicals to halogen radicals for the degradation of organic pollutants in the presence of other components, such as halides . Therefore, persulfate activation for the degradation of organic pollutants would be complicated and affected by shale components, which deserves an in-depth study in the future.…”
Section: Results and Discussionmentioning
confidence: 99%
“…•− radicals to halogen radicals for the degradation of organic pollutants in the presence of other components, such as halides. 82 Therefore, persulfate activation for the degradation of organic pollutants would be complicated and affected by shale components, which deserves an in-depth study in the future.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the self-decay and UV photolysis of N -chloramines, radicals in the UV/chlorine process can also be involved. Cl • can form chlorinated DBPs via direct addition, while both HO • and RCS can activate the precursors to increase the formation of DBPs. , Although the increased DCAN formation from two amino acids (i.e., l -arginine and l -histidine) during UV/chlorine treatment has been reported in previous studies, , it is attributed to nitrogen-containing side chains of l -arginine and l -histidine (i.e., guanidine and imidazole, respectively) but not amino moieties. Exploring the mechanisms for DCAN formation from amino compounds is necessary to understand the increased DCAN formation during UV/chlorine treatment, whereas it has remained largely unknown to date.…”
Section: Introductionmentioning
confidence: 83%